Relevansi Kebijakan Salary Policy Pada Dosen Pegawai Negeri Sipil di Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Republik Indonesia dengan Realitas Sosial dan Perubahan Zaman - Syukron, Nurkholis; Irawan, Andri (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Education is one of the most important components in supporting the life of the nation and state. Education in Indonesia is guaranteed by the 1945 Constitution of the Republic of Indonesia which is explicitly stated in the phrase